Fallacies and Topos in Public Critique: The Case of Gus Miftah on Twitter - Azza Naila, Suriya; Kurniawan, Muhammad Hafiz (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study examines the discourse surrounding Gus Miftah’s resignation as a presidential special envoy, emphasizing Twitter users’ remarks. This study focuses on how public debates and criticism toward Gus Mifath can be misleading and out of focus. This study aims to show that emotion and improper judgment can break the arguments rule in public debates. By using Martin Reisigl and Ruth Wodak’s theoretical framework on pragmatic fallacies and topoi and the theory of attitude in appraisal theory by Martin and White, the research identifies and analyzes argumentative strategies prevalent in public discourse. The findings reveal a significant presence of fallacies, including ad hominem which has dominant result 30.2% and ad populum 15.7% and topos of justice, disadvantage, and humanitarianism by score 10.7%, 9.7% and 9.7% from 113 data respectively can challenges power structures and result in political change. Situated within Indonesia’s socio-cultural context, the study highlights mostly those arguments fall into fallacies which means that they were fueled by emotions and misjudgment in attitude analysis found that 69.86% are about negative judgment and 13.4% negative appreciation. In addition, this research also found 45% in negative judgment and 16% in positive affect in topos. This result shows that although many comments are fueled by emotions and misjudgment, few of them still states their hope of change from Gus Miftah and the government who chose him as the presidential special envoy.